2004
DOI: 10.1161/01.cir.0000129317.12580.68
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Renal Transplant Recipients in the United States After Coronary Revascularization Procedures

Abstract: Background-Retrospective studies in dialysis patients have reported increased survival after coronary artery bypass (CAB) compared with coronary artery stenting and PTCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 20 publications
4
53
1
1
Order By: Relevance
“…Among patients with end-stage renal disease (ESRD), cardiac mortality is 10 to 30 times higher than in the general population. The mechanism of this association is not entirely known, but a higher prevalence of traditional risk factors in this population such as advanced age, hypertension and diabetes, contributes to accelerated atherosclerosis [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…Among patients with end-stage renal disease (ESRD), cardiac mortality is 10 to 30 times higher than in the general population. The mechanism of this association is not entirely known, but a higher prevalence of traditional risk factors in this population such as advanced age, hypertension and diabetes, contributes to accelerated atherosclerosis [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…However, these data are limited by the retrospective design and the inherent risk of procedure-related referral bias based on coronary anatomy and patient characteristics. 145 An updated analysis of USRDS data from 2003 to 2005 by the same authors, including patients treated with DES, found superior 12-month unadjusted postprocedural survival in patients on dialysis who received DES (69.7%) compared with CABG (66.6%) or non-DES PCI (63.6%). 146 However, unadjusted 36-month survival favored CABG over DES (42.0% versus 38.1%), especially among patients who received an internal mammary artery bypass conduit.…”
Section: Lentine Et Al Cardiac Disease Evaluation and Management Amonmentioning
confidence: 99%
“…22 Recent reports from the BMS era showed comparable long-term survival after percutaneous and surgical coronary revascularization procedures in renal transplant recipients. 23 The invasiveness of CABG contributes to an increased risk of in-hospital death, postoperative mediastinitis and postoperative stroke. 24 After the approval of SES, a benefit of less invasive revascularization by PCI over CABG was expected.…”
Section: Mortality After Coronary Revascularization In Dialysis Patientsmentioning
confidence: 99%